Digital heterotopias: simulation and realities in "La sombra cazadora" (Suso de Toro) and "Sueños digitales" (Edmundo Paz Soldán) - Pedrós-Gascón, Antonio Francisco (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
La sombra cazadora (De Toro 1995) and Sueños digitales (Paz Soldán 2000) are two recent examples of dystopic novels in Hispanic Literatures. In this article 1 will analyze how these authors depict what Baudrillard calls “le crime parfait”: the assasination of reality. 1 will focus on how the dialectics established between power and mass-media creates “reality” in postmodernity, and will conclude with the moral/social reading implied by both works. Every distopic narration is direct or indirectly connected to the society within which it is produced, and in which the author wants to denounce a current or future danger. National disenchantment seems to be the origin of both authors” denunciation. Disenchantment with the postrevolutionary Latin American Nation is found in the Bolivian author’s text, while the “childish democracy” that emerged from the Spanish Transition is found in the Galician author’s text.